Variable Expression of Programmed Cell Death Protein 1-Ligand 1 in Kidneys Independent of Immune Checkpoint Inhibition - Hakroush, Samy; Kopp, Sarah Birgit; Tampe, Désirée; Gersmann, Ann-Kathrin; Korsten, Peter; Zeisberg, Michael; Tampe, Björn (Frontiers in Immunology, 2021)
Context: Due to recent advantages in cancer therapy, immune checkpoint inhibitors (ICIs) are new classes of drugs targeting programmed cell death protein 1 (PD-1) or its ligand programmed cell death protein 1-ligand 1 (PD-L1) used in many cancer therapies. Acute interstitial nephritis (AIN) is a potential and deleterious immune-related adverse events (irAE) in the kidney observed in patients receiving ICIs and the most common biopsy-proven diagnosis in patients who develop acute kidney injury (AKI). Based on previous reports, AIN in patients receiving ICIs is associated with tubular positivity for PD-L1, implicating that PD-L1 positivity reflects susceptibility to develop renal complications with these agents. It remains unclear if PD-L1 positivity is acquired specifically during ICI therapy or expressed independently in the kidney. Methods: PD-L1 was analyzed in experimental mouse models of ischemia-reperfusion injury (IRI), folic acid-induced nephropathy (FAN), unilateral ureteral obstruction (UUO) and nephrotoxic serum nephritis (NTN) by immunostaining, SDS-PAGE and subsequent immunoblotting. In addition, we included a total number of 87 human kidney samples (6 renal biopsies with AIN related to ICI therapy, 13 nephrectomy control kidneys and 68 ICI-naïve renal biopsies with various underlying kidney diseases to describe PD-L1 expression. Results: We here report distinct PD-L1 expression in renal compartments in multiple murine models of kidney injury and human cases with various underlying kidney diseases, including ICI-related AIN and renal pathologies independent of ICI therapy. PD-L1 is frequently expressed in various renal pathologies independent of ICI therapy and could potentially be a pre-requisit for susceptibility to develop AKI and deleterious immune-related AIN. In addition, we provide evidence that tubular PD-L1 positivity in the kidney is associated with detection of urinary PD-L1+ tubular epithelial cells. Conclusion: Our study implicates that PD-L1 is frequently expressed in various renal pathologies independent of ICI therapy and could potentially be a pre-requisit for susceptibility to develop AKI and deleterious immune-related AIN. Because non-invasive detection of PD-L1+ cells in corresponding urine samples correlates with intrarenal PD-L1 positivity, it is attractive to speculate that further non-invasive detection of PD-L1+ cells may identify patients at risk for ICI-related AIN.